A Post-Revitalization Model Learning for Fort Willem I as an Open History Laboratory - Alfan Fikril Hakim; Rizka Cahyaning Arifin Putri; Aditya Ramadhan (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2026)
This article explores the revitalized Willem I Fort as an “Open History Laboratory” to support contextual history learning. Visiting historical buildings in person can help students understand history lessons empirically. The purpose of this study is to analyze the fort’s historical potential and formulate strategies for utilizing Willem I Fort as a dynamic contextual learning resource. The research method used is qualitative, specifically a literature review. The results indicate that Fort Willem I holds historical potential that can be incorporated into history education. The revitalization efforts support the optimization of its educational functions. The proposed strategies include inquiry-based educational zoning, implementation of Contextual Teaching and Learning (CTL), digitization of knowledge, and strategic collaboration. The transformation of Fort Willem I into an open history laboratory can synergize aspects of pure and applied history, supporting the improvement of historical literacy, awareness of cultural heritage preservation, and students’ critical thinking skills through direct interaction with material evidence from the past.